A framework for extracting, classifying, analyzing, and presenting information from semi-structured web data sources - Shaker, Mahmoud; Ibrahim, Hamidah; Mustapha, Aida; Abdullah, Lili Nurliyana (2010)
Extracting information from the web data sources becomes very important because the massive and increasing amount of diverse semi-structured information sources in the Internet that are available to users, and the variety of web pages making the process of information extraction from web a challenging problem. This paper proposes a framework for extracting, classifying, analyzing, and presenting semi-structured web data sources. The framework is able to extract relevant information from different web data sources, and classify the extracted information based on the standard classification scheme of Nokia products, which has been chosen as the case study.